Effect of Capital Structure, Tax Avoidance, and Firm Size on Firm Value with Dividend Payout Ratio as Moderating - Sekar Dewi Mula Wardani; Anggita Langgeng Wijaya; Heidy Paramitha Devi; Anissa Ayera (Profesional Muda Cendekia Publishing, 2022)
Infrastructure is an integrated part of national-level development and the axis of economic movement. The more intensive infrastructure development is carried out, the higher the competition between construction companies to obtain capital from investors. This study aims to analyze the effect of Capital Structure, Tax Avoidance, and Firm Size towards Firm Value with Dividend Payout Ratio as a Moderating Variable conducted on construction and building sub-sector companies listed on the Indonesia Stock Exchange in 2015-2019 period. This research was a quantitative research where data was processed using the SPSS 25 application. The population in this study was a construction and building sub-sector company that has gone public and published its financial or has been listed on the Indonesia Stock Exchange in 2015-2019 period. Determination of the sample using purposive sampling method. In this study there were 30 samples of companies. This study used multiple linear regression analysis and Moderated Regression Analysis (MRA). The results of this study indicate that: (1) Capital structure affects firm value; (2) Tax Avoidance does not affect firm value; (3) Firm Size affects firm value; (4) Dividend Payout Ratio is able to moderate the effect of capital structure towards firm value; (5) Dividend Payout Ratio is not able to moderate the effect of tax avoidance towards firm value; (6) Dividend Payout Ratio is not able to moderate the effect of firm size towards firm value. Keyword: Capital Structure, Tax Avoidance, Firm Size, Firm Value, Dividend Payout Ratio.